In vivo and in vitro Antidiabetic and Antioxidant Activity of Spirulina - Okechukwu, Patrick Nwabueze; Ekeuku, Sophia Ogechi; Sharma, Mridula; Chong, Pei Nee; Hor, Kuan Chan; Norazlina, Mohamed; Froemming, Gabriele Ruth Anisah (Wolters Kluwer - Medknow, 2019)
This study aims to evaluate the effect of spirulina, a biomass produced by cyanobacteria, on the level of plasma glucose, oxidative stress, and other biochemical parameters in diabetes in streptozocin (STZ) 50 mg/kg‑induced diabetic‑induced rat model. Materials and Methods: The in vitro antioxidant property of spirulina was assessed by measuring its ability to scavenge free radicals and reactive oxygen species (ROS) such as superoxide anion, nitric oxide, and hydroxyl and lipid peroxyl radicals. The inhibition of diabetic link enzymes alpha‑glucosidase, alpha‑amylase, and dipeptidyl peptidase‑4 inhibitor (DPP‑IV) were tested in vitro. Thirty female Sprague‑Dawley rats weighing 150–250 g were divided into five groups: normal, diabetes (negative control), metformin in single dose of 300 mg/kg, spirulina in a single dose of 300 mg/kg and spirulina combined with metformin at dose of 150 mg/kg, and spirulina at dose of 150 mg/kg (spirulina + metformin 300 mg/kg) (n = 6). After an acclimation period of 2 weeks, diabetes was induced in the rats through STZ intraperitoneal injection. Spirulina (300 mg/kg) was dissolved in water and was administered orally for 12 weeks, and the rats’ that plasma glucose level reached ≥11 mmol/L after 12 weeks treatment was selected for the study. After the treatment, the blood and liver were used for the evaluation of antioxidant enzyme activities, lipid, liver, kidney, and hematology profile. Results: Spirulina was able to reduce yperglycemia‑induced oxidative stress by reducing plasma glucose levels and scavenging or reducing the production of ROS and free radicals. It was also able to inhibit the activities of the alpha‑glucosidase, alpha‑amylase, and DPP‑IV. With this, it significantly reduced the effect of STZ on the liver and kidney at the organ level and on antioxidant enzymes at the cellular level. Conclusion: Spirulina is able to reduce the lipid, liver, and kidney disease markers in STZ‑induced rats and therefore is a potential supplement for diabetic patients. The antidiabetic effect of spirulina may be based on the antioxidant effect of the biomass as a whole, or it is based on specific bioactive components present in spirulina.